2014
DOI: 10.1530/eje-13-0696
|View full text |Cite
|
Sign up to set email alerts
|

Impact of insulins glulisine and aspart on postprandial glycemia after a high-glycemic index meal in children with type 1 diabetes

Abstract: Objective: According to current knowledge, glulisine insulin (GLU) has a slightly faster onset of action than aspart (ASP) insulin. Therefore, GLU might lead to a better postprandial profile than ASP following the consumption of high-glycemic index (H-GI) meals. The aim of this study was to assess differences in the action of GLU and ASP after the consumption of a H-GI meal in type 1 diabetic children treated with insulin pumps. Design: Fifty-six type 1 diabetic children of mean age 14.7G2.0 years were include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 24 publications
(20 reference statements)
0
9
0
1
Order By: Relevance
“…Postprandial glycemia is noted to be one of the most important predictors of HbA1c and is associated with the onset of complications [22]. Research has demonstrated that common childhood eating patterns, such as consuming a breakfast with a high glycemic index (i.e., cereal with milk), can have a substantial impact on glycemic control throughout the day and following night [23-25].…”
Section: Challenges To T1d Management and Glycemic Controlmentioning
confidence: 99%
“…Postprandial glycemia is noted to be one of the most important predictors of HbA1c and is associated with the onset of complications [22]. Research has demonstrated that common childhood eating patterns, such as consuming a breakfast with a high glycemic index (i.e., cereal with milk), can have a substantial impact on glycemic control throughout the day and following night [23-25].…”
Section: Challenges To T1d Management and Glycemic Controlmentioning
confidence: 99%
“…Mealtime management is critical for families who have young children with T1D. Serving healthy and balanced food is essential, because BG after meals is one of the most important predictors of long-term health (Dzygalo & Szypowska, 2014). In a pediatric sample, postprandial glucose readings were highest after breakfast (Boland et al, 2001) and may contribute to erratic glycemic variability through the next day (Nilsson, Radeborg, & Björck, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…According to Dżygało et al neither of insulin analogs: glulisine and aspart provide a stabilized glycemic profile after a h-GI meal. 25 The new formulation of insulin-faster aspart with the faster onset of appearance and the greater early exposure in comparison to aspart in children and adolescents comes to use in clinical practice. A statistically significant reduction in 2-hour postprandial glycemia after standardized meal was reported.…”
Section: Discussionmentioning
confidence: 99%